Structure Technology in the Sattra of Assam, India - Goswami, Nandita (International Journal of Psychosocial Rehabilitation, 2020)
The Sattra establishment of Assam is a product of their Vaisnavite motion started by Sankaradeva (1449-1568) towards the final decade of the fifteenth century. The organization has, since its beginning, been serving since the radiating power of spiritual activities of their Vaisnavites in and about Assam. Sattras are categorized under four crucial Sanghatis (denominations or even sub-sects) specifically, Purusha Sanghati, Nika Sanghati, Kala Sanghati along with Brahma Sanghati. The structural design of a Sattra is indicated with the occurrence of a Naamghar, a Manikut, also a Karapat and just two to a four row of Hatis. The very first phase of the development of Sattra institution started with Sankaradeva at 1469 A.D.. However, the super structure of this Sattra was increased throughout the centuries. It had been in the right time of both Satanandadeva, Madhavadeva along with Damodaradeva which Sattra establishment approached the next stage of its growth. The Sattra establishment took a certain monastic twist in the palms of Banxi-Gopaldeva who introduced several modifications within his KalabariSattra near the conclusion of the past century. The concluding phase of this development of the Sattra association came with expansion of imperial patronage to all major Sattras. The Sattras main functions would be to disperse Vaisnavism according to monotheistic principle, to commence disciples, to present ethic-devotional rules and codes of behavior to neophytes and to maintain religious festivals on various events. The Secondary purposes of the Sattra would be to observe that good social relation is preserved among the villagers, to create the soul ofco-operation, to offer sufficient facilities for its dissemination of early learning and also to distribute justice on all spiritual and social controversies. The current earnings of Sattra is principally derived from 2 sources-a) earnings from lands initially given by the tribes of those Pre-British times and afterwards verified and realized by the British authorities; b) earnings from spiritual to this led by disciples. The Part played with the Sattra establishment in different spheres, aside from faith, deserves note. Throughout its years of life, the Sattra has improved Assamese life socially and educationally and has contributed a excellent deal to the kingdom of literature as well as other arts. This paper will Attempt to Go over Structure tech of Sattra of Assam.